Umbilical artery lactate levels and associated maternal and newborn characteristics at Mulago National Referral Hospital: a cross-sectional observational study - Jolly Nankunda; Victor Ogik; Mark Muyingo; Moses Musooko (BMJ Open)
Objective To determine the maternal and newborn characteristics associated with high umbilical artery lactate levels at Mulago National Referral Hospital.Design Cross-sectional observational study.Setting Department of Obstetrics and Gynecology at a national referral hospital located in the capital of Uganda, Kampala.Participants We randomly selected 720 pregnant mothers at term who presented in labour and their newborn babies.Primary outcome Umbilical artery lactate level.Results During the study, there were 579 vaginal deliveries (18 instrumental) and 141 caesarean sections which met the inclusion criteria. One hundred and eighty-seven neonates (187) had high arterial lactate levels. The following factors were associated with an increased likelihood of high lactate concentration: male sex (adjusted OR (aOR)=1.71; 95% CI 1.16 to 2.54; p<0.05), primigravidity (aOR=2.78; 95% CI 1.89 to 4.08; p<0.001), meconium-stained liquor (aOR=5.85; 95% CI 4.08 to 8.47; p<0.001) and administration of oxytocin (aOR=1.97; 95% CI 1.00 to 3.77; p<0.05).Conclusion About a fifth of the babies born in Mulago National Referral Hospital during the study period had high umbilical artery lactate. The maternal-fetal factors significantly associated with high umbilical artery lactate levels included: baby’s sex, mother’s gravidity, meconium-stained amniotic fluid and oxytocin administration during labour.